A typology of the use of clicks - Brenzinger, Matthias; Shah, Sheena (Stellenbosch Papers in Linguistics Plus, 2023)
Click speech sounds were first identified as consonants in the 17th century. On his voyage to India in 1627, the English traveller and historian Sir Thomas Herbert stopped in southern Africa, where he met with Khoekhoe speakers at the Cape. He noticed that clicks were regular consonants in their language and represented them as such in his travelogue (Herbert 1638). Since then, click consonants have received thorough scholarly attention by linguists, many of whom have dedicated their lives to the study of click consonants. Click speech sounds are consonants in phoneme inventories of about 301 of the approximately 6,5002 languages spoken in the world today. These few languages, henceforth referred to as click-consonant-using (CU) languages, are found in southern and eastern Africa. In this squib we propose a typology of the different uses of click speech sounds in human communication.